Development of MRI techniques for the assessment of chronic kidney disease - Buchanan, Charlotte E. (2016)
It is well established that patients with Chronic Kidney Disease (CKD) are more susceptible to develop cardiovascular disease in comparison to the healthy population. This thesis aims to develop and apply MRI techniques to assess the human heart and kidney in patients with chronic kidney disease (CKD).